An examination of the role played by WiPSU in promoting women's participation and representation in governance in midlands province: the case of Gweru, Kwekwe and Zvishavane - Sibanda, Sipho (Midlands State University, 2018)
The purpose of this research was to examine the role played by WiPSU in promoting women's participation and representation in governance in the Midlands Province, with particular focus on Gweru, Kwekwe and Zvishavane. A qualitative research approach attempted to bring to light an understanding of the various dynamics that are shaping the level of women’s participation and representation in the political processes of the country. The three aforementioned areas were used to acquire population samples for data collection purposes and justify the findings of the study in addressing the challenge of women’s representation and participation in decision making processes. Appreciative of the fact that; the Midlands Province is a large geographical area to cover in limited time, the researcher’s data collection was thus largely informed by desk research which he comprehended by data collected through interviews with 9 purposivelyselected respondentsand self-administered questionnaires to 75 conveniently sampled respondents. These sampled respondents afforded the researcher the opportunity to acquire first-hand information and experiences that guided the findings of this study.The results presented in this study brought an understanding of the patriarchal, psychosocial, political and institutional factors militating against inclusive participation and representation of women in decision making structures in the political domain and also brought an appreciation of the significance of women in political process. The research also brought an appreciation of the role civil society is playing to complement government efforts in advancing the agenda for women’s participation and representation in leadership.